A QUALITATIVE RESEARCH ON CONSUMPTION AND RELIGION PERCEPTIONS OF WOMEN WHO VISIT PRAYER ROOMS IN SHOPPING MALLS - (:unkn) unknown (HITIT UNIV, 2020)
Consumption is a phenomenon that has a big area in human life. And religion is a phenomenon that affects human's actions. Therefore, it is inevitable that they affect each other. Their relationship has been a subject to the field of sociology of religion. Considering the psychological aspect of consumption, there is also a need for studies in the field of psychology of religion. This study is expected to contribute to filling this gap in the literature. In this study, it is aimed to determine the perceptions of consumption and religion and to analyze their relationship in detail. In order to do this, interviews with those who visit the prayer rooms in shopping malls and field observations are applied. The research is a phenomenological research. In order to measure the consumption and religious perceptions, observations were made in the field as well as semi-structured interviews. 33 women who came to the prayer mall of Akasya AVM between the start of the noon prayer and the evening prayer on March 16-17, 2019, and March 23-24, 2019 were interviewed. Content analysis was applied to the interview texts and observation notes. The validity and reliability are provided by blind coding, expert review, and direct quotes. The purposes of participants to go to shopping malls is shopping (%90), meeting with friends (%30), watching a movie (%18), wandering/killing time (%15), eating/drinking (%12), cultural and artistic activities (%6), discount (%3) and prayer hall (%3). The result of the questions about the waste of time and the time spent in the shopping mall indicates the value attributed to time in the eyes of the participants, and also shows that individuals may fail against the enchantment strategies of the shopping mall unless they are careful enough. Findings regarding wasting money in the shopping mall were similar to wasting time. It is found that the participants use religious mechanisms to avoid from both types of wasting. This means that the participants are aware of their religious responsibility for wasting time and money. However, they confess that they cannot be successful on this all the time. Although secular special day concepts and celebrations held in the shopping malls such as valentine day, new year's eve, etc. have a negative meaning for most of the participants, the majority of the participants states that they are obliged to stay with the short-term reactions towards the shopping malls, and the majority of the participants states that they have no alternative. On the other hand, there are two types of attitudes towards the concepts or activities held on religious special days: (1) criticizing these activities with the thought that they will serve capitalism and (2) supporting them claiming that they will increase the visibility of the religion in social life. Religious sensitivities during shopping are of great importance among participants. It has been observed that religious sensitivity in food shopping is at the top and it is also effective on clothing shopping to a large extent. When a prayer performed in the prayer hall of a shopping mall is compared with other prayers, three types of thoughts have emerged: (1)that the environment does not affect the feeling of prayer, (2)it feels more special when time is allocated between activities such as shopping and wandering, and (3) it negatively affects the feelings during the prayer because of the negative earthly environment. According to the results obtained from the research, it can be said that for most of the participants their expressions of consumption are based on religious grounds and references. Religion maintains its determining and indispensable position for Muslim individuals during consumption, as in all areas of life. Generally, individuals accept modern phenomenon so long as it corresponds with their own religious values.
Keywords: Psychology of Religion; Consumption; Perception; Shopping Mall; Prayer Room